1996
DOI: 10.1073/pnas.93.13.6731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a murine Ahr null allele: involvement of the Ah receptor in hepatic growth and development.

Abstract: The Ah receptor (AHR) is a ligand-activated transcription factor that mediates a pleiotropic response to environmental contaminants such as benzo [a]pyrene and 2, 3,7,8-tetrachlorodibenzo-p-dioxin. In an effort to gain insight into the physiological role of the AHR and to develop models useful in risk assessment, gene targeting was used to inactivate the murineAhr gene by homologous recombination. Ahr-l mice are viable and fertile but show a spectrum of hepatic defects that indicate a role for the AHR in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
579
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 800 publications
(607 citation statements)
references
References 33 publications
15
579
2
1
Order By: Relevance
“…Many such symptomatic discrepancies are apparent between the present report and previous reports. The other pathological effects observed in homozygous Ahr mutant mice will be discussed elsewhere in reference to previous reports from other laboratories (Fernandez-Salguero et al 1995;Schmidt et al 1996).…”
Section: Targeting Of the Ahr Gene By Homologous Recombinationmentioning
confidence: 85%
See 1 more Smart Citation
“…Many such symptomatic discrepancies are apparent between the present report and previous reports. The other pathological effects observed in homozygous Ahr mutant mice will be discussed elsewhere in reference to previous reports from other laboratories (Fernandez-Salguero et al 1995;Schmidt et al 1996).…”
Section: Targeting Of the Ahr Gene By Homologous Recombinationmentioning
confidence: 85%
“…Although two separate studies have already been published on mice which lack the AhR gene, these groups reported considerable phenotypic differences, but with consistent observations being a reduced liver weight and a loss of inducibility of the drug-metabolizing enzymes (Fernandez-Salguero et al 1995;Schmidt et al 1996). It has recently been reported that adult Ahr -/-mice became resistant to the toxic effects of TCDD in the thymus and liver (Fernandez-Salguero et al 1996).…”
Section: Introductionmentioning
confidence: 92%
“…In the population genomic study, CYP1A duplications were found in three of the four tolerant populations; in the three northern tolerant populations, individuals have up to eight CYP1A copies (Reid et al., 2016). Even in the absence of exogenous chemical exposure the AHR may help to maintain basal CYP1A expression; loss of AHR signaling in mice reduces this expression (Schmidt, Su, Reddy, Simon, & Bradfield, 1996). Thus, CYP1A duplications might have been favored in tolerant fish with suppressed AHR signaling to maintain constitutive levels of CYP1A needed for physiological functions.…”
Section: Ecological Considerationsmentioning
confidence: 99%
“…Because the [Ah] gene battery comprises at least six and probably many more genes, the AhR controls constitutive expression of several xenobiotic-metabolizing enzymes. AhR-null mice have been constructed by several laboratories 43,51,52 and these animals exhibited immune system impairment and hepatic fibrosis confirming that AhR has a developmental and physiological role. Activation of the AhR by polycyclic aromatic hydrocarbons (PAHs) and associated compounds is associated with disruption of multiple hormone systems resulting in developmental and reproductive impairment.…”
Section: Wwwnaturecom/tpjmentioning
confidence: 92%
“…Thus, mouse lines have also been constructed that lack Cyp1a2. 43,44 CYP1B1 shares many properties with CYP1A1 such as the metabolic activation of polycyclic aromatic hydrocarbons (PAHs). In addition to activating polycyclic aromatic hydrocarbons, CYP1B1 functions as a physiological regulator in that a deficiency in the enzyme has been linked to congenital glaucoma in humans.…”
Section: Wwwnaturecom/tpjmentioning
confidence: 99%